Study of Engine Propeller Matching for High-Speed Vessel with Gawn Series Propeller - Nurhadi Nurhadi; Hardi Zen; Sumarsono Sumarsono (EPI International Journal of Engineering, 2018)
At the stage of ship design, in addition of use up to date software can also need model test to verify the results of the calculation, such as resistance test, open water test, self propulsion test which associated powering of the ship. Beside of these, engines propeller matching is required to determine the load engine characteristics and ship speed associated propeller used. In this study, high speed vessel with Gawn series propeller type is used. Based on EPM results known that at 28 knots of speed, propeller has a high enough efficiency around 0.56 in rough hull condition. By using the CAT 280-8 engine, at 1000 rpm, ship speeds can reach about 30.5 knots and power requirements is 2400 kW.